2021
DOI: 10.5194/bg-2021-207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A seamless ensemble-based reconstruction of surface ocean pCO<sub>2</sub> and air–sea CO<sub>2</sub> fluxes over the global coastal and open oceans

Abstract: Abstract. We have estimated the air–sea CO2 fluxes (fgCO2) over the global ocean from the open sea to the continental shelves. Fluxes and associated uncertainty were computed from an ensemble-based reconstruction of CO2 sea surface partial pressure (pCO2) maps trained with observations from the Surface Ocean CO2 Atlas v2020 database. The ensemble mean (which is the best estimate provided by the approach) fits independent data well and a broad agreement between the spatial distribution of model-data differences… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 50 publications
(141 reference statements)
0
28
0
Order By: Relevance
“…In a broader context, Landschützer et al (2016) suggested that the carbon uptake tended to increase slightly in 1998-2011 in the Subtropical Indian Ocean (their figure 3). We will see that such a change in the CO 2 fluxes in this region is also revealed in the CMEMS-LSCE-FFNN model (Chau et al, 2021). Note that if at that location 27°S/55°E…”
Section: Comparison With a Low Bloom Year: 2005mentioning
confidence: 54%
See 2 more Smart Citations
“…In a broader context, Landschützer et al (2016) suggested that the carbon uptake tended to increase slightly in 1998-2011 in the Subtropical Indian Ocean (their figure 3). We will see that such a change in the CO 2 fluxes in this region is also revealed in the CMEMS-LSCE-FFNN model (Chau et al, 2021). Note that if at that location 27°S/55°E…”
Section: Comparison With a Low Bloom Year: 2005mentioning
confidence: 54%
“…In order to complement the results based on regional in-situ data and evaluate the CO 2 sink anomalies in this region back to 1996, we also used results from a neural network model that reconstructs monthly fCO 2 fields and air-sea CO 2 fluxes. The fCO 2 fields were obtained from an ensemble-based feed-forward neural network model (named CMEMS-LSCE-FFNNN) described in Chau et al (2021). To take into account the period in austral summer 2020 when the SEMB was particularly strong, we used the latest temporal extension of the model which relies on the most recent version of the SOCAT data-base (SOCAT-v2021, Bakker et al, 2021).…”
Section: Reconstructed Fco 2 and Air-sea Co 2 Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…This would allow an easy and rapid quality indicator for the selection of observations that may be used for XCO2 estimates, either using 400 a physics-based algorithm or a NN approach. variables are varied adequately (e.g., Chau et al 2021), or analytical estimates (Aires et al, 2004) should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The data products provided by Laruelle et al (2017) and Landschützer et al (2020b) -hereafter L17 and L20, respectively Most data-based estimates of oceanic CO2 uptake have considered only the open ocean (e.g., Rödenbeck et al, 2013;Landschützer et al, 2014;Iida et al, 2015;Denvil-Sommer et al, 2019;Gregor et al, 2019;Watson et al, 2020); however, coastal ocean CO2 uptake is estimated to be about 10% of the open-ocean figure (Laruelle et al, 2010;2014;Bourgeois et al, 2016;Roobaert et al, 2019;Chau et al, 2021) and may be changing at a different rate relative to open-ocean CO2 uptake (Laruelle et al, 2018). Therefore, augmenting global open-ocean pCO2(sw) data products to include the coastal ocean is quite valuable (Fay et al, 2021).…”
mentioning
confidence: 99%